Prey-related odor preference of the predatory mites Typhlodromalus manihoti and Typhlodromalus aripo (Acari: Phytoseiidae) - Gnanvossou, D.; Hanna, R.; Dicke, M. (2002)
Typhlodromalus manihoti and Typhlodromalus aripo are exotic predators of the cassava green mite Mononychellus tanajoa in Africa. In an earlier paper, we showed that the two predators were attracted to odors from M. tanajoa-infested cassava leaves. In addition to the key prey species, M. tanajoa, two alternative prey mite species, Oligonychus gossypii and Tetranychus urticae also occur in the cassava agroecosystem. Here, we used a Y-tube olfactometer to determine the attraction of the predators to odors from O. gossypii- or T. urticae-infested cassava leaves and their prey-related odor preference. T. aripo but not T. manihoti was slightly attracted to odors from O. gossypii-infested leaves. Both predator species showed a stronger response to odors from cassava leaves infested by M. tanajoa over odors from cassava leaves infested by O. gossypii. Neither predator species was attracted to odors from T. urticae-infested leaves and the predators preferred the odors from M. tanajoainfested leaves over those from T. urticae-infested leaves. When O. gossypii was present together with M. tanajoa on the same leaves or on different sets of leaves offered together as an odor source the two predators were attracted. In contrast, after mixing non-attractive odors from T. urticae-infested leaves with attractive odors from M. tanajoa-infested leaves, neither T. aripo nor T. manihoti was attracted. Ecological advantages and disadvantages of the predators' behavior and possible implications for biological control of M. tanajoa are discussed.